Development of modified diagnostic criteria for bacterial vaginosis at peripheral health centres in developing countries - Vineeta Mittal; Amita Jain; Yashodhara Pradeep (Journal of Infection in Developing Countries)
Introduction:  Bacterial vaginosis (BV) is the commonest cause of abnormal vaginal discharge in women of child-bearing age and is associated with increased susceptibility to HIV-AIDS and sexually transmitted diseases. In obstetrics, BV has been implicated in causing various complications. In clinical practice, BV is diagnosed using Amsel criteria and Nugent scoring. Using modified Amsel criteria, we determined that the fulfilling of any two instead of three criteria can be diagnostic of BV.